Mechanically oscillating sample under magnetic field gradients: MOS-NMR - Everton Lucas-Oliveira; Agide Gimenez Marassi; Arthur Gustavo Araújo-Ferreira; Edson Luiz Géa Vidoto; Aparecido Donizeti Fernandes de Amorim; Willian Andrighetto Trevizan; Tito José Bonagamba (Journal of Magnetic Resonance Open, 2022)
Nuclear Magnetic Resonance (NMR) has been widely used in Petroleum Science and Engineering to study geological formations (porous media) in laboratories or under well-logging conditions. In both cases, NMR is still evolving to provide more accurate data on well productivity. In well-logging, NMR is one of the main tools used in determining the economic viability of an oil well due to the reliability of measurements of fluid types, porosity, pore size, and permeability of the reservoir under analysis. There are two kinds of NMR well-logging techniques: Wireline and Logging While Drilling (LWD). In the latter, due to the drilling process, measurements are made with the NMR tool translating, vibrating and, in some cases, rotating relatively to the geological formation. To understand the behavior of NMR signals measured under LWD conditions, not yet including displacement and drill vibration, we have recently developed a single-sided magnet, probes, and a mechanical system that emulates a relative sinusoidal motion between the sample and the applied magnetic field. This equipment was used to emulate a LWD tool operating under normal pressure and temperature conditions.